A review of electrolyzer-based systems providing grid ancillary services: current status, market, challenges and future directions - Cozzolino, Raffaello; Bella, Gino (Frontiers in Energy Research, 2024)
Concerns related to climate change have shifted global attention towards advanced, sustainable, and decarbonized energy systems. While renewable resources such as wind and solar energy offer environmentally friendly alternatives, their inherent variability and intermittency present significant challenges to grid stability and reliability. The integration of renewable energy sources requires innovative solutions to effectively balance supply and demand in the electricity grid. This review explores the critical role of electrolyzer systems in addressing these challenges by providing ancillary services to modern electricity grids. Electrolyzers traditionally used only for hydrogen production have now emerged as versatile tools capable of responding quickly to grid load variations. They can consume electricity during excess periods or when integrated with fuel cells generate electricity during peak demand, contributing to grid stability. Therefore, electrolyzer systems can fulfill the dual function of producing hydrogen for the end-user and offering grid balancing services, ensuring greater economic feasibility. This review paper aims to provide a comprehensive view of the electrolyzer systems’ role in the provision of ancillary services, including frequency control, voltage control, congestion management, and black start. The technical aspects, market, projects, challenges, and future prospects of using electrolyzers to provide ancillary services in modern energy systems are explored.